Application of nanoparticles in biofuels: An overview. (1st February 2019) - Sekoai, Patrick T.; Ouma, Cecil Naphtaly Moro; du Preez, Stephanus Petrus; Modisha, Phillimon; Engelbrecht, Nicolaas; Bessarabov, Dmitri G.; Ghimire, Anish
Highlights: A comprehensive overview of nanoparticles used in biofuel processes. Nanomaterials for biohydrogen, biogas, biodiesel and bioethanol production increase. Nanoparticles are revealed to be effective in suppressing inhibitory compounds. Nanoparticles could pave a way for the establishment of a viable biofuel sector. Abstract: Biofuels are fast advancing as alternative sources of renewable energy due to their non-polluting features and cost-competitiveness in comparison to fossil fuels. However, in order to fast-track their development, focus is shifting towards the use of technologies that will maximize their yields. Nanoparticles are gaining increasing interest amongst researchers due to their exquisite properties, which enable them to be applied in diverse fields such as agriculture, electronics, pharmaceuticals and food industry. They are also being explored in biofuels in order to improve the performance of these bioprocesses. This review critically examines the various studies in literature that have explored nanoparticles in biofuel processes such as biohydrogen, biogas, biodiesel and bioethanol production, towards enhancing their process yields. Furthermore, it elucidates the different types of nanomaterials (metallic, nanofibers and nanotubes) that have been used in these bioprocesses. It also evaluates the effects of immobilized nanoparticles on biofuels such as biodiesel, and the ability of nanoparticles to effectively suppress inhibitory compounds under certain conditions. A short section is included to discuss the factors that influence the performance of nanoparticles on biofuels production processes. Finally, the review concludes with suggestions on improvements and possible further research aspects of these bioprocesses using nanoparticles.